Sustained delivery of a heterodimer bone morphogenetic protein-2/7 via a collagen hydroxyapatite scaffold accelerates and improves critical femoral defect healing. (May 2023) - Liu, Yang; Puthia, Manoj; Sheehy, Eamon J.; Ambite, Ines; Petrlova, Jitka; Prithviraj, Sujeethkumar; Oxborg, Maria Wimer; Sebastian, Sujeesh; Vater, Corina; Zwingenberger, Stefan; Struglics, André; Bourgine, Paul E.; et al.
Abstract: Despite the glimmer of hope provided by the discovery and commercialization of bone morphogenetic protein-2 (BMP-2) as a bone graft substitute, side effects related to the use of supraphysiological doses have hindered its clinical usage. In this study, we compared the osteoinductive potential of BMP-2 homodimer with a heterodimer of BMP-2/7, both delivered via a collagen-hydroxyapatite (CHA) scaffold delivery system, with the aim to reduce the overall therapeutic BMP doses and the associated side-effects. We first show that the incorporation of hydroxyapatite in collagen-based BMP delivery systems is pivotal for achieving efficient BMP sequestration and controlled release. Using an ectopic implantation model, we then showed that the CHA+BMP-2/7 was more osteoinductive than CHA+BMP-2. Further evaluation of the molecular mechanisms responsible for this increased osteoinductivity at an early stage in the regeneration process indicated that the CHA+BMP-2/7 enhanced progenitor cell homing at the implantation site, upregulated the key transcriptomic determinants of bone formation, and increased the production of bone extracellular matrix components. Using fluorescently labelled BMP-2/7 and BMP-2, we demonstrated that the CHA scaffold provided a long-term delivery of both molecules for at least 20 days. Finally, using a rat femoral defect model, we showed that an ultra-low dose (0.5 µg) of BMP-2/7 accelerated fracture healing and performed at a level comparable to 20-times higher BMP-2 dose. Our results indicate that the sustained delivery of BMP-2/7 via a CHA scaffold could bring us a step closer in the quest for the use of physiological growth factor doses in fracture healing. Statement of significance: Incorporation of hydroxyapatite (HA) in a collagen scaffold dramatically improves bone morphogenic protein (BMP) sequestration via biophysical interactions with BMP, thereby providing more controlled BMP release compared with pristine collagen. We then investigate the molecular mechanisms responsible for increased osteoinductive potential of a heterodimer BMP-2/7 with is clinically used counterpart, the BMP-2 homodimer. The superior osteoinductive properties of BMP-2/7 are a consequence of its direct positive effect on progenitor cell homing at the implantation site, which consequently leads to upregulation of cartilage and bone related genes and biochemical markers. An ultra-low dose of BMP-2/7 delivered via a collagen-HA (CHA) scaffold leads to accelerated healing of a critical femoral defect in rats while a 20-times higher BMP-2 dose was required to achieve comparable results. Graphical abstract: Image, graphical abstract